2019
DOI: 10.3389/fphar.2019.00818
|View full text |Cite
|
Sign up to set email alerts
|

A New Use for an Old Drug: Carmofur Attenuates Lipopolysaccharide (LPS)-Induced Acute Lung Injury via Inhibition of FAAH and NAAA Activities

Abstract: Acute lung injury (ALI), characterized by a severe inflammatory process, is a complex syndrome that can lead to multisystem organ failure. Fatty acid amide hydrolase (FAAH) and N -acylethanolamine acid amidase (NAAA) are two potential therapeutic targets for inflammation-related diseases. Herein, we identified carmofur, a 5-fluorouracil-releasing drug and clinically used as a chemotherapeutic agent, as a dual FAAH and NAAA inhibitor. In Raw264.7 macrophages, carmofur effectively reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 57 publications
(66 reference statements)
2
32
0
Order By: Relevance
“…The suppressive effect of OEA on PPAγ expression was also demonstrated in vitro by incubating HLF hepatic cells for 2 h with 10 µM OEA ( Figure 5 d,e). Moreover, the ceramidase inhibitor Carmofur, which increases OEA cell level by inhibiting fatty acid hydrolases [ 56 ], induced both alone and in association with OEA, a strong decrease in PPARγ expression ( Figure 5 d,e).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The suppressive effect of OEA on PPAγ expression was also demonstrated in vitro by incubating HLF hepatic cells for 2 h with 10 µM OEA ( Figure 5 d,e). Moreover, the ceramidase inhibitor Carmofur, which increases OEA cell level by inhibiting fatty acid hydrolases [ 56 ], induced both alone and in association with OEA, a strong decrease in PPARγ expression ( Figure 5 d,e).…”
Section: Resultsmentioning
confidence: 99%
“…In our study, we observed that OEA-induced a significant decrease of PPARγ expression both in vivo and in vitro. In this latter system the link between OEA and PPARγ was reinforced by using Carmofur, a fatty acid hydrolase inhibitor that can block OEA degradation and, thus, increase OEA level in the cell [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Western blot assay and RT-qPCR were performed as descriptions. 24,25 Cell Apoptosis Assay T cells were isolated from BALB/c mice spleens by nylon wool-elution, as described previously. 23 T cells were cultured with RPMI 1640 medium, HSC-CM, or shC3 HSC-CM in 12-well plates, respectively, and then stimulated with 1 μg/mL of anti-CD3 mAb and CD28 (R&D Systems, Minneapolis, MN, USA).…”
Section: Knockdown Of C3 In Hscsmentioning
confidence: 99%
“…These chemicals showed selective inhibitory potency but with a poor plasma stability, which restricted its systematic administration (Bandiera et al, 2014;Petracca et al, 2017). Based on the structure of pyrrolidine derivatives, our research group identified a class of novel inhibitors with oxazolidone moiety, represented by F96 and F215, with nanomolar potency against NAAA (Yang et al, 2015;Li et al, 2017;Ren et al, 2017;Wu et al, 2019;Zhou et al, 2019). Migliore et al reported third-generation NAAA inhibitors based on a benzothiazole-piperazine scaffold that is stable in mouse plasma and liver microsomes (Migliore et al, 2016).…”
Section: Discussionmentioning
confidence: 99%